2012
DOI: 10.1104/pp.112.207308
|View full text |Cite
|
Sign up to set email alerts
|

Group III-AXTHGenes of Arabidopsis Encode Predominant Xyloglucan Endohydrolases That Are Dispensable for Normal Growth      

Abstract: The molecular basis of primary wall extension endures as one of the central enigmas in plant cell morphogenesis. Classical cell wall models suggest that xyloglucan endo-transglycosylase activity is the primary catalyst (together with expansins) of controlled cell wall loosening through the transient cleavage and religation of xyloglucan-cellulose cross links. The genome of Arabidopsis (Arabidopsis thaliana) contains 33 phylogenetically diverse XYLOGLUCAN ENDO-TRANSGLYCOSYLASE/ HYDROLASE (XTH) gene products, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 95 publications
(142 reference statements)
1
61
0
Order By: Relevance
“…Deletion of this loop significantly increased the transglycosylation/hydrolysis ratio of the enzyme, making it structurally and functionally more XET-like (11). This loop insertion is likewise found in two homologous A. thaliana XEHs of Group III-A (12).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Deletion of this loop significantly increased the transglycosylation/hydrolysis ratio of the enzyme, making it structurally and functionally more XET-like (11). This loop insertion is likewise found in two homologous A. thaliana XEHs of Group III-A (12).…”
Section: Discussionmentioning
confidence: 84%
“…S5) previously observed for plant and microbial XEHs (12,18). In addition to the mixture of oligosaccharides expected from cleavage at the unbranched ␤(134)- Table 2, and gymnosperm transcripts in Group III-A are denoted by their accession number at TIGR (24).…”
Section: Limit Digestion Products From Mixed Linkage Glucans-further mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, XTH27 is involved in the cell wall modification of tracheary elements at a specific stage of rosette leaf development and is essential for tertiary vein development (Matsui et al, 2005), whereas XTH31 is involved in cell wall modification and cell elongation through modulating xyloglucan endotransglucosylase (XET) action under Al stress (Zhu et al, 2012). However, XTH31 is an XTH for which xyloglucan endohydrolase (XEH) activity has been predicted (Baumann et al, 2007), and in our previous report, we demonstrated that XTH31 produced heterologously in Pichia pastoris has high XEH activity but low XET activity in vitro (Zhu et al, 2012), which is in accordance with Kaewthai et al (2013), who reported that XTH31 is a predominant hydrolase using the in vitro activity assays and enzyme product analysis, as well as the use of a fluorogenic substrate in vivo. Unexpectedly, however, the xth31 mutant has very low XET action and activity (Zhu et al, 2012).…”
mentioning
confidence: 95%
“…These activities could modify xyloglucan chain length as well as its connections to microfibrils and have been shown to alter cell wall extension (Nishitani and Vissenberg, 2007;Miedes et al, 2013;Park and Cosgrove, 2015). The family also includes enzymes that show predominantly endohydrolase activity, using water as the final acceptor, but their physiological role is still unclear (Kaewthai et al, 2013). It is also unclear if xyloglucan can be hydrolyzed by plant endoglucanases from other families.…”
mentioning
confidence: 99%